Improved treatment results of children with B‐cell non‐Hodgkin lymphoma: A report from the Japanese Pediatric Leukemia/Lymphoma Study Group B‐NHL03 study. Issue 7 (13th February 2014) - Tsurusawa, Masahito; Mori, Tetsuya; Kikuchi, Akira; Mitsui, Tetsuo; Sunami, Shosuke; Kobayashi, Ryoji; Takimoto, Tetsuya; Saito, Akiko; Watanabe, Tomoyuki; Fujimoto, Junichiro; Nakazawa, Atsuko; Ohshima, Kouichi; et al.
<x xml:space="preserve">Abstract</x> Background Previous Japanese studies of childhood B‐cell non‐Hodgkin lymphoma (B‐NHL) have shown a favorable outcome, though the study size was too small to effectively assess the efficacy and safety of treatment for childhood B‐NHL. Procedure We performed a nation‐wide prospective B‐NHL03 study to assess the efficacy and safety of short‐pulse intensive chemotherapy for children with B‐NHL. They were stratified into four treatment groups according to disease stage, tumor resectability and bone marrow/CNS involvement: Group 1 with all resected stage I/II, Group 2 with non‐resected stage I/II, Group 3 with stage III & CNS‐negative stage IV, and Group 4 with CNS‐positive stage IV & Burkitt leukemia. Treatment duration was 2 courses for Group 1, 4 courses for Group 2, and 6 courses for Groups 3 and 4, respectively. CNS irradiation was omitted in all patients. Results The follow‐up time ranged from 0.8 to 88 months, with a median of being 45 months. For 321 patients analyzed in this study, overall survival and event‐free survival (EFS) at 4 years was 92.7% and 87.4%, respectively. The 4‐year EFS according to treatment group were 94% for Group 1 (n = 17), 98% for Group 2 (n = 103), 84% for Group 3 (n = 111), and 78% for Group 4 (n = 90). There was no significant difference in outcome by histology. Therapy‐related death occurred in three patients in remission. Conclusions Our nationwide large‐scale study resulted in a cure rate above 90% with <1% toxic death in childhood B‐NHL. Pediatr Blood Cancer 2014;61:1215–1221. © 2014 Wiley Periodicals, Inc.